Memristors: A Spin–Orbit‐Torque Memristive Device (Adv. Electron. Mater. 4/2019). (9th April 2019) - Zhang, Shuai; Luo, Shijiang; Xu, Nuo; Zou, Qiming; Song, Min; Yun, Jijun; Luo, Qiang; Guo, Zhe; Li, Ruofan; Tian, Weicheng; Li, Xin; Zhou, Hengan; et al.
Abstract : A domain wall can be driven back and forth in a continuous manner in a ferromagnetic (FM) layer by applying in‐plane positive or negative current pulses along the heavy‐metal (HM) layer, as reported by Long You and co‐workers in article number1800782 . Utilizing the spin‐orbit torque that the current exerts on the CoFeB magnetization results in memristive (synapse‐like) functions.